2005
DOI: 10.1016/s0002-9440(10)62289-4
|View full text |Cite
|
Sign up to set email alerts
|

CCR2-Mediated Recruitment of Fibrocytes to the Alveolar Space after Fibrotic Injury

Abstract: Bone marrow-derived cells are known to play important roles in repair/regeneration of injured tissues, but their roles in pathological fibrosis are less clear. Here, we report a critical role for the chemokine receptor CCR2 in the recruitment and activation of lung fibrocytes (CD45 ؉ , CD13 ؉ , collagen 1 ؉ , CD34 ؊ ). Lung fibrocytes were isolated in significantly greater numbers from airspaces of fluorescein isothiocyanate-injured CCR2 ؉/؉ mice than from CCR2 ؊/؊ mice. Transplant of CCR2 ؉/؉ bone marrow into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
430
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(459 citation statements)
references
References 29 publications
25
430
3
1
Order By: Relevance
“…In humans, both CXCL8 and CCL2 concentrations were found to be increased in blood (Ziegenhagen et al, 1998a;Suga et al, 1999;Fujiwara et al, 2012) and bronchoalveolar lavage fluid (BALF) (Capelli et al, 2005;Antoniou et al, 2006;Baran et al, 2007) of IPF patients compared with healthy volunteers and correlated with lung function (Capelli et al, 2005;Emad and Emad, 2007;Martina et al, 2009;Vasakova et al, 2009), disease progression (Ziegenhagen et al, 1998b;Totani et al, 2002), and outcome (Shinoda et al, 2009;Richards et al, 2012). Furthermore, several studies suggested an involvement of the chemokine CCL2 in the pathogenesis of IPF, notably through its action on resident pulmonary fibroblast and circulating fibrocytes, promoting the generation of abundant extracellular matrix in the lungs (Gharaee-Kermani et al, 1996;Phillips et al, 2004;Moore et al, 2005;Inomata et al, 2014). Such strong evidence involving CXCL8 in the pathogenesis of the disease are lacking, although this chemokine is thought to act as a pro-fibrotic factor in IPF via the promotion of exacerbated angiogenesis (Strieter et al, 2002;Rosenkilde and Schwartz, 2004;Antoniou et al, 2006;Martina et al, 2009;Cui et al, 2010).…”
Section: Cxcl8 and Ccl2 Concentrationsmentioning
confidence: 99%
“…In humans, both CXCL8 and CCL2 concentrations were found to be increased in blood (Ziegenhagen et al, 1998a;Suga et al, 1999;Fujiwara et al, 2012) and bronchoalveolar lavage fluid (BALF) (Capelli et al, 2005;Antoniou et al, 2006;Baran et al, 2007) of IPF patients compared with healthy volunteers and correlated with lung function (Capelli et al, 2005;Emad and Emad, 2007;Martina et al, 2009;Vasakova et al, 2009), disease progression (Ziegenhagen et al, 1998b;Totani et al, 2002), and outcome (Shinoda et al, 2009;Richards et al, 2012). Furthermore, several studies suggested an involvement of the chemokine CCL2 in the pathogenesis of IPF, notably through its action on resident pulmonary fibroblast and circulating fibrocytes, promoting the generation of abundant extracellular matrix in the lungs (Gharaee-Kermani et al, 1996;Phillips et al, 2004;Moore et al, 2005;Inomata et al, 2014). Such strong evidence involving CXCL8 in the pathogenesis of the disease are lacking, although this chemokine is thought to act as a pro-fibrotic factor in IPF via the promotion of exacerbated angiogenesis (Strieter et al, 2002;Rosenkilde and Schwartz, 2004;Antoniou et al, 2006;Martina et al, 2009;Cui et al, 2010).…”
Section: Cxcl8 and Ccl2 Concentrationsmentioning
confidence: 99%
“…Fibrocytes express CCR1, CCR2, CCR4, CCR5, and CCR7, [11][12][13][14] and their migration is regulated in part by chemokines. 5 To dissect the mechanism of fibrocyte trafficking in response to liver injury, a CCR1 (or CCR2) receptor knockout mouse was crossed with a Col-Luc mouse and used for BM transplantation into lethally irradiated wild-type mice ( Figure 3D) 18 and undergo several stages of maturation.…”
Section: Ccr2 and Ccr1 Regulate Fibrocyte Migration In Response To CCmentioning
confidence: 99%
“…9,10 Migration of fibrocytes to fibrotic lungs and kidneys is regulated on several levels including profibrogenic growth factors (eg, TGF-␤1) and chemokines (CCL2, CCL3, and CCL12). Reduced fibrocyte recruitment has been observed in CCR5 Ϫ/Ϫ and CCR2 Ϫ/Ϫ mice 11,12 and correlates with attenuation of lung fibrosis. Migration of fibrocytes to fibrotic kidneys is regulated by chemokine receptors CCR2, CCR7, and CXCR4 13,14 and is highly restricted to damaged organs.…”
mentioning
confidence: 92%
“…In HMCs, the CCR2 receptor also mediates MCP-1-induced ICAM-1 levels [17]. Therefore, HMCs produce a functionally active CCR2 receptor as previously shown both in vitro [8][9][10][11][12] and in vivo [13][14][15]35] in other nonmononuclear cell types.…”
Section: Discussionmentioning
confidence: 76%
“…However, a functionally active CCR2 receptor has been demonstrated in other cell types both in vitro [8][9][10][11][12] and in vivo [13][14][15], suggesting that MCP-1 may have other functional effects beyond monocyte recruitment [16]. Accordingly, we recently reported that in human mesangial cells (HMCs) MCP-1 binding to CCR2 induces intercellular adhesion molecule-1 (ICAM-1) production, leading to enhanced monocyte adhesion [17].…”
Section: Introductionmentioning
confidence: 99%